Optimalisasi Edukasi Keluarga Binaan Penderita Hipertensi Di Puskesmas Anak Air, Kota Padang Dengan Mengidentifikasi Masalah Kesehatan Keluarga Melalui Family Assesment Tools Dan Wellness Plan - Savita Kholifatunnisa (GLOBAL SCIENTS PUBLISHER, 2024)
Hypertension is a health problem that contributes to the highest mortality and morbidity rates in the world. Apart from medical treatment, hypertension treatment also takes the form of lifestyle modifications, including limiting salt consumption, physical activity, getting enough rest, avoiding stress, and lowering to a normal BMI. This fostered family program was implemented in the families of patients who were patients at the Anak Air Community Health Center, Padang City from 20 August to 5 September 2024. The activities carried out included analysis of family assessment tools, family wellness plans, and education. The results of the APGAR I & II assessment showed that the patient's family was classified as a highly functional family and had good relationships with all family members. The results of identifying internal health problems found that patients still did not understand that hypertension could be passed on to other family members. Apart from that, patient knowledge regarding lifestyle, exercise and diet that is good for their disease is still lacking. The known external problem is that family members still do not have knowledge and awareness about health, and have not made lifestyle changes such as eating foods with balanced nutrition and exercising regularly. Based on these problems, a wellness plan is designed. Lifestyle modifications are carried out by calculating Total Calorie Requirements (KKT), daily fluid requirements, exercise and stress management. Based on KKT calculations, patients must meet daily calorie needs of 1,237 kcal per day. Patients are also advised to meet their daily fluid requirements of 2,160 cc/day (8-9 small glasses or sidewalk glasses) and are given education regarding stress management steps.